Pediatric Intensive Care Hybrid-Style Clinical Round During COVID-19 Pandemic: A Pilot Study - Temsah, Mohamad-Hani; Alhboob, Ali; Abouammoh, Noura; Al-Eyadhy, Ayman; Aljamaan, Fadi; Alsohime, Fahad; Alabdulhafid, Majed; Ashry, Ahmad; Bukhari, Ahmad; ElTahir, Omer; Jamal, Amr; Halwani, Rabih; et al. (Frontiers in Pediatrics, 2021)
Background: With the evolving COVID-19 pandemic and the emphasis on social distancing to decrease the spread of SARS-CoV-2 among healthcare workers (HCWs), our pediatric intensive care unit (PICU) piloted the integration of Zoom meetings into the clinical rounds. We aimed to explore the feasibility of these hybrid virtual and physical clinical rounds for PICU patients. Methods: This is a mixed quantitative and qualitative deductive thematic content analysis of narrative responses, conducted in the PICU of a single tertiary-care academic center. Participants were multidisciplinary PICU HCWs.The aim was to pilot the Integration of Zoom meeting into the clinical daily PICU rounds. For the quantitative part, we gathered the details of the daily PICU hybrid rounds in terms of times, number of HCWs, and type of files shared through Zoom. For the qualitative part, open-ended questions were used. Results: The physical round had statistically significantly less time (34.68 ± 14.842 mins) as compared to the Zoom round (72.45 ± 22.59 mins), p < 0.001. The most shared component in the virtual round was CXR (93.5%). 31 HCW participated in the focused group discussions and were included in the analysis. Some of the HCWs' perceived advantages of the hybrid rounds were enabling the multidisciplinary discussions, lesser round interruptions, and practicality of the virtual discussions. The perceived challenges were the difficulty of the bedside nurse to attend the virtual round, decreased teaching opportunities for the trainees, and decreased interactions among the team members, especially if the video streaming was not utilized. Conclusions: Multidisciplinary hybrid virtual and physical clinical rounds in PICU were perceived as feasible by HCWs. The virtual rounds decreased the physical contact between the HCWs, which could decrease the possibility of SARS-CoV-2 spread among the treating team. Still, several components of the hybrid round should be optimized to facilitate the virtual team-members' interactions and enhance the teaching experience.